Evaluating soil erodibility parameters with mini-JET under various soil moisture conditions - Nguyen, Gia Huynh Truong (Kansas State University, 2016)
Soil erosion is one of the main reasons for agricultural land degradation in the world. Losses of land because of high soil erosion rates and rapidly expanding population result in significant reduction of cultivated land area per capita, and shortage of food on the global scale. Soil erosion can be a major source of sediment in the aquatic systems leading to reduction of organism population and poor water quality. Many factors affect soil erodibility, such as, soil properties, rainfall, topographic features, land use, and management practices, among others. The impacts of soil moisture content, however, are not well understood and. therefore, the primary goal of this study was to quantify two soil erodibility parameters, the erodibility coefficient and critical shear stress, under different soil moisture conditions using the jet erosion test (JET). The JET test uses the apparatus (called mini-JET) that creates an impinging jet of water into the soil and records the resulting scour depth over time. The scour depth time series are then fitted into a non-linear soil erosion equation, yielding the sought values of erodibility parameters. For this study, more than 40 soil samples were collected from several sites in Kansas, processed, and prepared to conduct JET tests in the lab setting. The effects of tillage and soil moisture content were of interest to this study. The results showed varied effects of soil type and sample soil moisture condition on the scour depth development and parameters sensitivity. The critical shear stress decreased and the erodibility coefficient increased with the increase of initial moisture content for clay loam soil, while critical shear stress did not change for sandy loam soil. The study also revealed higher erosive properties of soil collected from the tilled field compared to the no-till field.
Keywords: erodibility coefficient; critical shear stress; JET test; soil loss; erosive propertiessoil erosion